A interiorização da Perícia Criminal Federal - Mesquita, Rogério Laurentino de (2012)
This research focuses on the internalization of the Criminalistics (Forensic Service) of the Federal Police, which consists of a project to open scientific and technical units to perform forensic examinations in some cities in the interior of Brazil where there are police stations of the Federal Police. After the opening of the first units in the interior of the country, some positive results have been achieved. However, it also emerged undesirable situations and negative aspects that were not provided for. The objective of this study was to evaluate the advantages and disadvantages of installing of technical-scientific units within the country for the administration of federal forensics. The survey was conducted with 59 heads of forensic units of the capitals of Member States and of some cities in the interior of the country. The study showed that some positive results have been achieved, as faster service and better interaction with the forensic service users. But it has been found also that there are problems related to infrastructure, human resources and materials in the units of the interior of the country. After this study it was possible to conclude that the continuation of the program of internalization of federal forensics depends on the achievement of the necessary investments preliminarily in human and material resources to that currently existing units may have the appropriate conditions for its functioning.